The histone demethylase KDM3A regulates the transcriptional program of the androgen receptor in prostate cancer cells - Wilson, S; Fan, L; Sahgal, N; Qi, J; Filipp, F (Impact Journals, 2017)
The lysine demethylase 3A (KDM3A, JMJD1A or JHDM2A) controls transcriptional networks in a variety of biological processes such as spermatogenesis, metabolism, stem cell activity, and tumor progression. We matched transcriptomic and ChIP-Seq profiles to decipher a genome-wide regulatory network of epigenetic control by KDM3A in prostate cancer cells. ChIP-Seq experiments monitoring histone 3 lysine 9 (H3K9) methylation marks show global histone demethylation effects of KDM3A. Combined assessment of histone demethylation events and gene expression changes presented major transcriptional activation suggesting that distinct oncogenic regulators may synergize with the epigenetic patterns by KDM3A. Pathway enrichment analysis of cells with KDM3A knockdown prioritized androgen signaling indicating that KDM3A plays a key role in regulating androgen receptor activity. Matched ChIP-Seq and knockdown experiments of KDM3A in combination with ChIP-Seq of the androgen receptor resulted in a gain of H3K9 methylation marks around androgen receptor binding sites of selected transcriptional targets in androgen signaling including positive regulation of KRT19, NKX3-1, KLK3, NDRG1, MAF, CREB3L4, MYC, INPP4B, PTK2B, MAPK1, MAP2K1, IGF1, E2F1, HSP90AA1, HIF1A, and ACSL3. The cancer systems biology analysis of KDM3A-dependent genes identifies an epigenetic and transcriptional network in androgen response, hypoxia, glycolysis, and lipid metabolism. Genome-wide ChIP-Seq data highlights specific gene targets and the ability of epigenetic master regulators to control oncogenic pathways and cancer progression.